(3Yjhf GdCfHGA aj WHbGJ GdCWHGAs - (3GHf CHj GUjHYI , ehab GdOjf CHh GdYHGS CMeO Hf GdbGSe Hf NdjaI Hf jhfS GdSYOj GdNRQLj,J (B668 (3g` s
(3ChdgG (B:s
(3GdMeO ddg fGTQ GdCee , hefTF GdQee , HGQF GdfSe , heHQF GdSbe , eNQL GdNdGFb HdWb UfYg Edi GdhLhO ef GdYOe s
(3BNQgG (B:s
(3Je gPG GdcJGH hGdMeO ddg JYGdi Ydi jO CMbQ GdYHGO ejNGjjd Hf TeGS LQLS Gdedci hcGf GdaQGZ efg fgGQ GdSHJ hbJ GdXgQ KGfi jhe ai TgQ QHjY GdChd SfI CQHY hSHYjf hCda s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ YfGhjjf GdCHhGH hHOGjGJ GdabQGJ HeOGO CMeQ s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs